(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Objective:-The objective of this study is to conduct a comprehensive trial assessing the marginal integrity and final setting properties of zirconia crowns across five generations, aiming to provide valuable insights into the evolution of zirconia-based restorations. Methodology: A randomized controlled trial was designed involving five different groups of zirconia crowns representing distinct generations of zirconia ceramics. Each group consisted of a sample size of 50 zirconia crowns fabricated using CAD/CAM technology following standardized protocols. Marginal integrity was evaluated using stereomicroscopy, with measurements taken at 100x magnification to assess the fit and adaptation of the crowns to the tooth structure. Results:-Preliminary analysis indicates variations in marginal integrity and final setting properties across the five generations of zirconia crowns. The first-generation zirconia crowns exhibited discrepancies in marginal fit and minor inconsistencies in final setting, primarily attributed to the manufacturing techniques and material composition. Subsequent generations showed improvements in marginal adaptation, with reduced marginal discrepancies and enhanced final setting characteristics. The latest generation of zirconia crowns demonstrated superior marginal integrity and optimal final setting, reflecting advancements in material processing and CAD/CAM technology. Conclusion:-The evolution of zirconia crowns across five generations has led to significant improvements in marginal integrity and final setting properties. These advancements are attributed to refinements in material composition, manufacturing techniques, and CAD/CAM technology. The findings of this trial underscore the importance of continuous innovation in restorative dentistry and provide valuable insights for clinicians in selecting the most suitable zirconia crowns for optimal clinical outcomes.